Shell Traffic Games: Effectiveness, Relevancy and Currency - Liew, T.; Ming, S.; Sim, S.; Pillai, Kamala Vainy; Ho, P. (Curtin Consultancy Services (Malaysia) Sdn Bhd, 2013)
This consultancy report was commissioned by Sarawak Shell Berhad (Shell) to review the effectiveness of Shell Traffic Games (STG) in Sarawak. The aim was to assess the effectiveness of STG in raising road safety awareness, knowledge and behavior among participants; to evaluate the relevancy and currency of STG, and present recommendations thereof. The study draws attention to the fact that STG was launched by Shell as part of its corporate social responsibility (CSR) endeavour since 1963, with the primal objective of educating young Malaysians on road safety behavior, and inadvertently, in the long run contributing towards the reduction of road injuries and fatalities in the country.